Digital representation and Occupy Wall Street's challenge to political subjectivity. (November 2014) - Creech, Brian
This article considers the ways in which practices of digital representation were deployed in the Occupy Wall Street movement, arguing that acts of self-representation render intelligible not just the politics of a movement like Occupy Wall Street but also make sensible the relations of power such projects are immersed within. Building upon the notion that the specific power of the movement was exercised via a situated understanding of representation, this essay investigates how a digitally mediated sensibility made the broader critiques at the core of the Occupy movement not only intelligible to those inside and outside the movement but also offered a mode of subject constitution that pushed against liberal notions of political subjectivity.